Photonic-Assisted Microwave Frequency Measurement With Adjustable Channel Bandwidth Based on Spectrum-Controlled Brillouin Phase Shift - Di Wang (IEEE, 2021)
A photonics-based channel bandwidth tunable microwave frequency measurement (MFM) is analyzed and verified, which is implemented based on the principle of the frequency-to-phase-slope mapping (FTPSM) in stimulated Brillouin scattering (SBS). The spectrum-controlled Brillouin phase shift curve is created by using an optical frequency comb (OFC) pump instead of a single pump. As a result, the Brillouin phase shift response is superimposed to further realize a flexible and adjustable measurement bandwidth. Meanwhile, thanks to the relationship between the OFC pump and the unknown signal, the frequency measurement can be achieved by the property of monotonous frequency-to-phase-slope mapping. A proof-of-concept experiment is performed to verify the feasibility of the approach. By changing the number of OFC lines, the channel bandwidths of 500, 700, or 900 MHz are demonstrated, with a measurement error lower than 35 MHz. We believe that this FTPSM-based MFM system is a promising solution for radio frequency (RF) channelized receiver.